Soap CharOl (Soap Charcoal Oil) Innovation of Oil and Used Cooking Oil Soap - Najma Rosita Asahy; Fasya Kamilatun Nuha; Mudhiah Dhiyaulhaq; Rizna Syafika Putri; Ana Jundiya Muthia Hamzah (SMA Trensains Muhammadiyah Sragen, 2023)
People's behavior in consuming used cooking oil repeatedly is very dangerous for health because it is carcinogenic which can trigger cancer in humans. In addition, used cooking oil waste is not managed properly, instead it is disposed of carelessly so that it has a negative impact on the environment. The need for cooking oil for industry and households is increasing, so that the waste cooking oil produced also increases. Used cooking oil is a serious waste that needs to be handled. With this, the researcher conducted an experiment in the form of making soap from waste cooking oil. The purpose of this study was to determine the process of making liquid laundry soap for household appliances by used cooking oil and charcoal. The cooking oil is purified by using an adsorbent in the form of activated charcoal and then processed into liquid soap using a base in the form of KOH. The addition of lemon essence as aroma, cleans stains, lifts fat, and kills germs, as well as yellow food coloring to improve product quality. The method used is quantitative analysis method. Parameters used in soap making include pH testing, foam stability, and organoleptic tests of aroma and color. The results of the analysis of soap are pH test value 10, foam stability value 50%, organoleptic of color test is yellow and the aroma of essence lime. Keywords: charcoal, essence, soap, used cooking oil